1978
DOI: 10.1007/bf01886292
|View full text |Cite
|
Sign up to set email alerts
|

The etiology of neurosensory hearing defects in preterm infants

Abstract: We retrospectively investigated the influence of gestational age, perinatal risk, and the duration of incubator care periods in 193 surviving preterm infants with a gestational age between 28 and 36 weeks raised in our intensive care nursery incubators from 1965--1967. 24 (12.4%) of the children showed definite neurosensory hearing defects, which were particularly encountered in the high frequencies. No correlation could be substantiated between hearing difficulties and hyperbilirubinemia, streptomycin applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…45,46 Three such studies (since the 1974 statement by the American Academy of Pediatrics' Committee on Environmental Health 5 ) that investigated the synergism of aminoglycosides and noise exposure had conflicting results. [47][48][49] In one, all five cases of moderate-to-severe sensorineural hearing loss were in infants treated with kanamycin and kept in incubators, suggesting a synergistic response. 47 In addition, 52% of 56 incubator-treated children with normal 46 assessed hearing at 6.5 years of age in 98 preterm NICU graduates.…”
Section: Noise-induced Hearing Lossmentioning
confidence: 97%
“…45,46 Three such studies (since the 1974 statement by the American Academy of Pediatrics' Committee on Environmental Health 5 ) that investigated the synergism of aminoglycosides and noise exposure had conflicting results. [47][48][49] In one, all five cases of moderate-to-severe sensorineural hearing loss were in infants treated with kanamycin and kept in incubators, suggesting a synergistic response. 47 In addition, 52% of 56 incubator-treated children with normal 46 assessed hearing at 6.5 years of age in 98 preterm NICU graduates.…”
Section: Noise-induced Hearing Lossmentioning
confidence: 97%
“…The reference microphone which is placed on the top of the incubator has a switch to turn on and off the ANC by gradually producing zero output and freezing the filter coefficients, as seen in Eqns. (2) To measure global ANC performance at uniformlyspaced three-dimensional (3-D) locations inside the incubator, a 3-D grid with movable bars to hold (1,4,5) and (8,4,5) positions. This grid is custom-made to fit the incubator shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Premature infants are therefore at high risk for environmentally-induced hearing loss. Three to five percent of extremely premature survivors are profoundly deaf 2,3 , while approximately 52% of infants with normal hearing who are placed in incubators exhibit changes in their audiograms that are consistent with minor acoustic trauma 4 . Kenworthy et al found that approximately one-third of 266 NICU residents exhibited hearing impairment and/or speech language problems 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hearing losses can always be fdund, they appear to be no greater nor more numerous than controls in, for example, musicians (Petrovic et al, 1979;Axelsson and Lindgren, 1981), mine locksmiths (Janisch, 1978), modern college students (Carter et al, 1978), children who live near airports (Fisch, 1981), incubator babies (Stennert et al, 1978;Winkel et al, 1978;Stewart and Abramovich, 1979), hearing aid users (Markides and Aryee, 1978), or even ambulance personnel (Johnson et al, 1980) and fire fighters (Reischl et al, 1981) who are exposed for short periods to siren noise at up to 115 dB SPL and whose daily 8-hr equivalent levels (L g8 8 h ) may near 100 dBA.…”
Section: Measurement Of Exposurementioning
confidence: 99%